Weight increase in people with cystic fibrosis on CFTR modulator therapy is mainly due to increase in fat mass - Mouzaki, Marialena; Dupuis, Annie; Avolio, Julie; Griffin, Katherine; Ratjen, Felix; Tullis, Elizabeth; Gonska, Tanja (Frontiers in Pharmacology, 2023)
Background: Ivacaftor, the first CFTR modulator drug, leads to significant long-term improvement in lung function and weight gain. The mechanism as well as the long-term impact of ivacaftor on weight, resting energy expenditure (REE) and body composition remains to be explored. Methods: This prospective observational study included 18 people with CF (pwCF) (age: median (range) 20 (6-58) years) carrying at least one CFTR gating mutation commencing ivacaftor. Assessments of body composition, REE and laboratory investigations were performed at baseline and 6, 12 and 24 months after treatment initiation. Results: Treatment with ivacaftor was associated with a significantly positive change in BMI z-score at 24 months. Fat mass (mean (95% CL) of 6.5 kg (4.0; 9.0) from baseline, p=0.0001), but not fat-free mass changed under ivacaftor treatment. There was a significant positive correlation between weight and fat mass change. Overall, there was no significant change in measured REE from baseline (mean (95% CL) of 108 kcal/d (-12;228), p=0.07) in our cohort. Pancreatic function and other nutritional markers did not change with treatment, with the exception of an increase in serum vitamin A levels (p=0.006). Conclusion: The weight gain observed in ivacaftor treated pwCF is predominantly secondary to increases in fat mass warranting early counseling of people starting on CFTR-modulating treatment with respect to healthy diet and physical exercise.